2022
DOI: 10.3889/oamjms.2022.8329
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Perceptions and Acceptance of Online Learning during the COVID-19 Pandemic in Indonesia

Abstract: BACKGROUND: The COVID-19 pandemic has changed the order of life in various aspects of life, including the field of education in Indonesia.  AIM: The purpose of the study was to determine student perceptions and acceptance of the online learning process during the COVID-19 pandemic. METHODS: The research is in the form of a survey using Google Forms about the perception and acceptance of online lectures during the COVID-19 pandemic for nursing students at universities in Indonesia, a questionnaire s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…Nonetheless, a systematic review of online learning during the COVID-19 pandemic found that, on average, students in the health sciences expressed more negative than positive perceptions (Abdull Mutalib et al, 2022). Findings are congruent with numerous studies conducted in the Philippines (Oducado & Soriano, 2021), Jordan (Maqableh & Alia, 2021), and Indonesia (Pramana et al, 2022;Simanullang et al, 2021) that tackle the experiences of students in the virtual setup. Most medical students in Jeddah and India said online learning affected their clinical skills (Ibrahim et al, 2021;Khan et al (2021).…”
Section: Discussionsupporting
confidence: 85%
“…Nonetheless, a systematic review of online learning during the COVID-19 pandemic found that, on average, students in the health sciences expressed more negative than positive perceptions (Abdull Mutalib et al, 2022). Findings are congruent with numerous studies conducted in the Philippines (Oducado & Soriano, 2021), Jordan (Maqableh & Alia, 2021), and Indonesia (Pramana et al, 2022;Simanullang et al, 2021) that tackle the experiences of students in the virtual setup. Most medical students in Jeddah and India said online learning affected their clinical skills (Ibrahim et al, 2021;Khan et al (2021).…”
Section: Discussionsupporting
confidence: 85%
“…Another example is the mobile training program on immunization for nurses and doctors (ADVT). (Pramana et al, 2022), (Rajasekaran Sriman Narayana Iyengar, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Kebijakan tersebut dilakukan untuk memutus rantai penyebaran virus Covid-19 (Hajerina et al, 2022;Hidayat et al, 2020;Nafrin & Hudaidah, 2021;Olivia et al, 2020;Yunitasari & Hanifah, 2020). Dengan adanya kebijakan tersebut, pemerintah dan lembaga terkait harus menyiapkan alternatif untuk proses pendidikan bagi peserta didik maupun mahasiswa yang skearang tidak bisa melaksanakan proses pembelajaran atau proses pendidikan pada suatau lembaga pendidikan (Cahaya et al, 2022;Mulyono et al, 2021;Nafrin & Hudaidah, 2021;Pramana et al, 2022).…”
Section: Pendahuluanunclassified